2014
DOI: 10.1021/bi500508z
|View full text |Cite
|
Sign up to set email alerts
|

Loop Interactions during Catalysis by Dihydrofolate Reductase from Moritella profunda

Abstract: Dihydrofolate reductase (DHFR) is often used as a model system to study the relation between protein dynamics and catalysis. We have studied a number of variants of the cold-adapted DHFR from Moritella profunda (MpDHFR), in which the catalytically important M20 and FG loops have been altered, and present a comparison with the corresponding variants of the well-studied DHFR from Escherichia coli (EcDHFR). Mutations in the M20 loop do not affect the actual chemical step of transfer of hydride from reduced nicoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…It is possible that it is more favorable, in terms of pyrimethamine resistance, to have mutations occur at position pairs that induce a smaller fluctuation response of FG loop when perturbed simultaneously, (i.e., restricting the dynamics) than the average fluctuation response of individual perturbations applied one at a time. This is in agreement with previous work which showed that point mutations to two of the FG loop amino acids in E.coli resulted in a > 30 fold decrease in the steady state hydride transfer rate constant as compared to the wild-type [ 47 ]. This could additionally explain the pervasive and persistent nature of these mutations appearing globally in pfDHFR proteins.…”
Section: Resultssupporting
confidence: 93%
“…It is possible that it is more favorable, in terms of pyrimethamine resistance, to have mutations occur at position pairs that induce a smaller fluctuation response of FG loop when perturbed simultaneously, (i.e., restricting the dynamics) than the average fluctuation response of individual perturbations applied one at a time. This is in agreement with previous work which showed that point mutations to two of the FG loop amino acids in E.coli resulted in a > 30 fold decrease in the steady state hydride transfer rate constant as compared to the wild-type [ 47 ]. This could additionally explain the pervasive and persistent nature of these mutations appearing globally in pfDHFR proteins.…”
Section: Resultssupporting
confidence: 93%
“…M20 loop motions generally do not appear to play a significant role in MpDHFR, which likely remains in a closed conformation for all complexes in the catalytic cycle. 49,50 In TmDHFR, the FG loop is buried in the dimer interface, apparently locking the enzyme in an open conformation (Fig. 2).…”
Section: The Role Of Dhfr Motionsmentioning
confidence: 99%
“… 50 Furthermore, despite its increased flexibility and contrary to EcDHFR, which cycles through the closed and occluded conformations, 4 , 34 MpDHFR does not appear to undergo major conformational change during progression through the reaction cycle. 51 , 52 Here, we report the kinetic properties of ‘light’ and ‘heavy’ MpDHFR. The MpDHFR kinetic isotope effect is minimal at physiological temperature, but in contrast to other non-psychrophilic DHFR homologues, its magnitude increases sharply with temperature.…”
Section: Introductionmentioning
confidence: 99%